Experience capitalization: We learn the most from the challenges we face - Macuiane, Messias A. (Technical Centre for Agricultural and Rural Cooperation, 2019)
I was one of the participants who joined the experience capitalization workshops in Maputo in 2017. I was chosen to join because, as the only M&E officer in the ProAQUA project being implemented in Mozambique, I am also responsible for knowledge management. It was good to get an invitation, but before I went I had to do an Internet search. To be frank, I did not know what “experience capitalization” was all about, and I thought it was necessary to get a clearer idea if I was to make the best of these meetings.